Research on the Characteristics of Thermosyphon Embankment Damage and Permafrost Distribution Based on Ground-Penetrating Radar: A Case Study of the Qinghai–Tibet Highway - Shunshun Qi; Guoyu Li; Dun Chen; Fujun Niu; Zhizhong Sun; Gang Wu; Qingsong Du; Mingtang Chai; Yapeng Cao; Jianwei Yue (Remote Sensing, 2023)
In order to research the special embankment (thermosyphon embankment) damages and the distribution of permafrost under the Qinghai–Tibet Highway (QTH) embankment. The section K2952–K2953, which is a typical representative of the QTH, was chosen for the detection and research of the permafrost and embankment damages in order to determine the sources of the damages. In this study, the performance characteristics of the embankment, the active layer, and the permafrost table found in ground-penetrating radar (GPR) images were researched, combined with multi-source. According to the research findings, the construction of the embankment in this section has stabilized the effect on the permafrost table. Under the embankment of the unemployed thermosyphon section, the permafrost distribution has good structural integrity and continuity, with the permafrost table at a depth of around 5 m. The continuity of the permafrost distribution under the embankment in the thermosyphon section was poor, and there was localized degradation, with the permafrost table being approximately 6 m deep. The main cause of the irregular settlement and other damage in this section is the presence of a loose area at the base of the embankment. Although the thermosyphon on both sides of the embankment also plays a role in lifting the permafrost table, it is not ideal for managing the damage to high embankments where the type of permafrost under the embankment is high-temperature permafrost with a high ice content and where the sunny–shady slope effect is obvious. The research results described in this article can therefore provide a crucial foundation for the detection of highway damage and permafrost under embankments in permafrost regions in the future.